COX-2 inhibitors for cancer treatment in dogs - De Nardi, Andrigo Barboza; Raposo, Talita Mariana Morata [UNESP]; Huppes, Rafael Ricardo [UNESP]; Daleck, Carlos Roberto [UNESP]; Amorim, Renée Laufer [UNESP] (My University, 2011)
Cancer is one of the main causes of death in canines and felines, and this fact is probably related to the increase in the longevity of these species. The longer the animals live, the higher the exposure to carcinogenic agents will be. With the high incidence of cancer in companion animals, new studies are currently being performed with the aim of finding therapeutic options which make the complete inhibition of the development of neoplasms in animals possible in the future. The correlation of cyclooxygenase-2 (COX-2) whith the development of cancer opens the way for the use of new therapeutic approaches. This relationship has been suggested based on various studies which established an association between the chronic use of nonsteroidal anti-inflammatory drugs (NSAID) and a decrease in the incidence of colon carcinoma. As cancer progresses, COX-2 participates in the arachidonic acid metabolism by synthesizing prostaglandins which can mediate various mechanisms related to cancer development such as: increase in angiogenesis, inhibition of apoptosis, suppression of the immune response, acquisition of greater invasion capacity and metastasis. Accordingly, overexpression of this enzyme in tumors has been associated with the most aggressive, poorprognosis cancer types, especially carcinomas. Therefore, treatments which use COX-2 inhibitors such as coxibs, whether administered as single agents or in combination with conventional antineoplastic chemotherapy, are an alternative for extending the survival of our cancer patients. © 2011 PVJ.
Keywords: Canine; Coxibs; Cyclooxygenase-2; Tumor